One-Pot Syntheses of [c2]Daisy-Chain Rotaxane Networks via Thiol-Ene Reaction and Its Application to Gel Electrolyte for Secondary Battery - Risako Kamoto; Kenjiro Onimura; Kazuhiro Yamabuki (Reactions)
A new topological material, the [c2]daisy-chain rotaxane network, was successfully synthesized via a thiol-ene reaction between a [c2]daisy-chain rotaxane, which consists of a host–guest compound (H–G compound) where a crown ether and a secondary ammonium salt are linked, and a multi-branched thiol compound. The resulting network polymer exhibited higher compressive strength compared to one without the [c2]daisy-chain rotaxane. Additionally, the neutralized [c2]daisy-chain rotaxane network, in which the ammonium salt was neutralized and there was no interaction with the crown ether, showed increased rigidity compared to its state before neutralization. Furthermore, a gel electrolyte was prepared by impregnating the [c2]daisy-chain rotaxane network with an organic electrolyte containing dissolved lithium salts, and its ionic conductivity was investigated. As a result, high ionic conductivity was achieved despite the high polymer content.